LONGITUDINAL RELATIONSHIP BETWEEN SLEEP HEALTH AND PAIN SYMPTOMS AMONG COMMUNITY-DWELLING OLDER ADULTS. (11th November 2018) - Chen, T; Lee, S; Gray, M; Saito, Y; Chan, A; Buxton, O M
Abstract: We investigated the longitudinal relationship between sleep health and a spectrum of pain outcomes among community-dwelling older adults. Data came from the Nihon University Japanese Longitudinal Study of Aging (N=2888) and the Panel on Health and Aging of Singaporean Elderly (N=2111). Poor sleep health was operationalized as having insufficient sleep duration (<6hours), insomnia symptom, and/or non-restorative sleep (vs. none of these: good sleep health). Pain was characterized as having any-pain, multiple pain locations, and pain-related disability. Covariates included sociodemographics, smoking, nap habit, depressive symptoms, comorbidity, and body mass index. Baseline poor sleep health predicted any-pain, multiple pain locations, and pain-related disability at follow-up, although cross-cultural differences were observed. Moreover, among those without pain at baseline, poor sleep health predicted new-onset of any pain later on, and vice versa. Improving sleep health of older adults may improve pain-related outcomes and help intervene on the vicious cycle of poor sleep and pain.